2012
DOI: 10.2215/cjn.02360312
|View full text |Cite
|
Sign up to set email alerts
|

Dialysis Search Filters for PubMed, Ovid MEDLINE, and Embase Databases

Abstract: SummaryBackground and objectives Physicians frequently search bibliographic databases, such as MEDLINE via PubMed, for best evidence for patient care. The objective of this study was to develop and test search filters to help physicians efficiently retrieve literature related to dialysis (hemodialysis or peritoneal dialysis) from all other articles indexed in PubMed, Ovid MEDLINE, and Embase.Design, setting, participants, & measurements A diagnostic test assessment framework was used to develop and test robust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Most references discourage its use at a creatinine clearance , 30 mL/min. 1,2 Recently, we showed that with appropriate dose reduction, metformin can be safely administered to patients with creatinine clearances as low as 15 mL/min without metformin or lactate concentrations increasing. 3,4 One patient in this cohort was also on hemodiafiltration (HDF) and had no elevation of metformin or lactate concentrations.…”
Section: Pharmacokinetics Of Metformin In Patients Receiving Regular mentioning
confidence: 99%
“…Most references discourage its use at a creatinine clearance , 30 mL/min. 1,2 Recently, we showed that with appropriate dose reduction, metformin can be safely administered to patients with creatinine clearances as low as 15 mL/min without metformin or lactate concentrations increasing. 3,4 One patient in this cohort was also on hemodiafiltration (HDF) and had no elevation of metformin or lactate concentrations.…”
Section: Pharmacokinetics Of Metformin In Patients Receiving Regular mentioning
confidence: 99%
“… Clinical conditions (Damarell, Tieman, Olver, & Currow, ; Damarell, Tieman, Sladek, et al., ; Hayman & Tieman, ; Hildebrand et al., , ; Iansavichus et al., ; Jenuwine & Floyd, ; Li & Lu, ; Shaheem & Tieman, ; Wilczynski & Haynes, ) Clinical disciplines (Brown et al., ; Durão, Kredo, & Volmink, ; Garg et al., ; Gill, Roberts, Wang, & Heneghan, ; Iansavichus et al., ; Jenuwine & Floyd, ; Li & Lu, ; Olaussen, Semple, Oteir, Todd, & Williams, ; Pols, Bramer, Bindels, van de Laar, & Bohnen, ; Sladek, Tieman, Fazekas, Abernethy, & Currow, ; Van de Glind, van Munster, Spijker, Scholten, & Hooft, ) Clinical interventions (Haslinghuis‐Bajan et al., ; Iansavichus et al., ; Kirk, Damarell, Tieman, & Harvey, ; Lee, Iansavichus et al., ) Demography (Hooijmans, Tillema, Leenaars, & Ritskes‐Hoitinga, ; Kastner, Wilczynski, Walker‐Dilks, McKibbon, & Haynes, ; Leclercq, Leeflang, van Dalen, & Kremer, ; Moerman, Deurenberg, & Haafkens, ; Song, Simonsen, Wilson, & Jenkins, ; Stewart et al., ; Tieman, Lawrence, Damarell, Sladek, & Nikolof, ) Geography (Ayiku et al., ; Pienaar, Grobler, Busgeeth, Eisinga, & Siegfried, ; Valderas, Mendivil, Parada, Losada‐Yanez, & Alonso, ) Health care delivery issues (Hempel et al., ; Lokker et al., ; McKibbon et al., ; Mesgarpour, Muller, & Herkner, 2012a, 2012b; Simon, Hausner, Klaus, & Dunton, ; Tanon et al., ; Varela‐Lema, Punal‐Rioboo, Accion, Ruano‐Ravina, & Garcia, ; Wilczynski & Haynes, ) Non‐clinical patient and carer issues (Johnson, Tongbram, Ndirangu, Ogden, & Bay, ; Petrova, Sutcliffe, Fulford, & Dale, ; Rogers, Bethel, & Boddy, ; Selva et al., ; Tieman, Hayman, &a...…”
Section: Resultsmentioning
confidence: 99%
“…All search filters were reported in the published literature with the exception of two unpublished conference posters (Damarell, Tieman, Olver, et al., ; Kirk et al., ) and one unpublished report (Shaheem & Tieman, ). A significant number of the topic filters (16/54; 30%) have been implemented into websites as one‐click, hyperlink searches (Damarell, Tieman, Olver, et al., ; Damarell, Tieman, Sladek, et al., ; Hayman & Tieman, ; Kirk et al., ; Shaheem & Tieman, ; Sladek et al., ; Tieman et al., ) or in the form of a search portal allowing users to enter their own search terms in combination with the filter (Brown et al., ; Garg et al., ; Hildebrand et al., , ; Iansavichus et al., , , ; Lee, Iansavichus et al., ; Tieman et al., ). Some are provided as search strings on websites for direct copy and paste into database search boxes (Lokker et al., ; McKibbon et al., ; Song et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations